Community formation in the Asean: an analysis of regional cooperation against piracy, terrorism and air pollution - Abdullahi, Ashraf Elfatih; Hossain, Ishtiaq (IIUM Press, 2017)
Regionalism and regional integration has become a common theme in international politics; states are realising that there is an advantage in regional collectivism. The E.U. is one of the mature examples in successful regional identity formation and integration. This study specifically focuses on the Association of Southeast Asian Nations (ASEAN), which has come to be regarded as one of the best experiments in regionalism in the developing world. This study uses variables which focus on cooperation as a tool for join behaviour at the inter-state level, ultimately leading to interdependence and a community of states where peaceful coexistence and co-dependence is a social norm. This study addresses how cooperation and trust lead to identity formation by studying mainly three areas of cooperation: piracy, terrorism and air pollution. Notwithstanding the limitations of ASEAN, member states have achieved increasing cooperation in the mentioned specific areas of piracy, terrorism, and air pollution through policy coordination and common action. This in turn has translated into a great deal of trust at various levels including leadership, administrative and the public level. The trust intensity might differ from one area of cooperation to another, however, overall, ASEAN members have learned to trust each other further due to the level of cooperation. Therefore this has translated into a larger sense of community through regional identity formation among member states. Trust and identity are reciprocal and reinforcing processes; the dynamic and positive relationship leads to mutual trust and collective identity. In its analysis of ASEAN cooperation, document analysis was used and data were obtained from primary sources, including ASEAN public records, declarations, speeches, conferences and others. In addition to that, publications in the form of books, journals, and papers written on ASEAN were utilised to examine cooperative action. Finally, regional newspapers and key interviews were employed as a way of obtaining insider perspectives regarding the issues being studied. This study has found that there is an unambiguous commitment among ASEAN member states to build a moral trust environment, where assured reliability is a common currency. All three areas examined: piracy, terrorism and air pollution showed increased commitment and synchronized action from individual member states. This in turn has transformed into the building of a common regional identity and community formation.